Radar-derived Surface Mass Balance at Derwael Ice Rise, Dronning Maud Land, Antarctica - Drews, Reinhard; Matsuoka, Kenichi; Martín, Carlos; Callens, Denis; Bergeot, N; Pattyn, Frank (PANGAEA, 2025)
This dataset provides surface mass balance estimates (also referred to as surface accumulation rates) derived from shallow radar stratigraphy of Derwael Ice Rise located in Dronning Maud Land, Antarctica. The underlying assumption is that the radar-detected stratigraphy is isochronal-representing former snow surfaces that have been buried since deposition. By correlating these isochrones with a dated firn core, an age can be assigned to each layer. Combined with a density-depth profile, also obtained from the firn core, this allows the estimation of the temporally averaged surface mass balance rate. This rate varies spatially with the depth of the isochrone. In this case, the surface mass balance estimates represent an average over the 21 years preceding 2012 CE. Spatial variation in accumulation is among others influenced by orographic effects induced by the topography of the ice rise. These data have been used as forcing for a model predicting patterns in the deeper radar stratigraphy, but they can also be used, e.g., to investigate the dependency of surface mass balance on surface slope and weather patterns in general.
Keywords: Antarctica; Derwael Ice Rise; GPR; GPR data; Surface accumulation rate; Surface Mass Balance